Hodgkin lymphoma is as common as non‐Hodgkin lymphoma in HIV‐positive patients with sustained viral suppression and limited immune deficiency: a prospective cohort study1. Issue 4 (23rd September 2014) - Hoffmann, C; Hentrich, M; Gillor, D; Behrens, G; Jensen, B; Stoehr, A; Esser, S; van Lunzen, J; Krznaric, I; Müller, M; Oette, M; Hensel, M; et al.
<x xml:space="preserve">Abstract</x> Objectives The incidence of HIV‐related non‐Hodgkin lymphoma (NHL) but not that of Hodgkin lymphoma (HL) has been declining. The aim of the study was to compare HIV‐infected patients with NHL and HL with respect to antiretroviral therapy (ART) exposure at the time of lymphoma diagnosis. Methods HIV‐infected patients with NHL and HL included in a prospective multicentre cohort study since January 2005 were compared with respect to ART exposure and viral load at the time of lymphoma diagnosis. Results As of 31 December 2012, data for 329 patients with NHL and 86 patients with HL from 31 participating centres were available. Patients with HL were more likely to be on ART (73.5% vs. 39.1%, respectively; P < 0.001) and more frequently had a viral load below the detection limit (57.3% vs. 27.9%, respectively; P < 0.001) than patients with NHL. The proportion of patients with HL was 8.0% in ART‐naïve patients, 34.8% in patients with current HIV RNA < 50 HIV‐1 RNA copies/mL, and 50.0% in patients with both HIV RNA < 50 copies/mL for > 12 months and a CD4 cell count of > 200 cells/μL. Of note, 45.8% of all patients with NHL were not currently on ART and had a CD4 count of < 350 cells/μL. Conclusions This prospective cohort study shows that HL was as common as NHL in patients with sustained viral suppression and limited immune deficiency. In contrast to NHL, the majority of patients with HL were on effective ART, suggesting that ART provides insufficient protection from developing HL. The high proportion of untreated patients with NHL suggests missed opportunities for earlier initiation of ART.